Strong preference of BRCA1 protein to topologically constrained non-B DNA structures - Brázda, Václav; Hároníková, Lucia; Liao, Jack C C; Fridrichová, Helena; Jagelská, Eva B (BMC molecular biology, 2016)
BACKGROUND: The breast and ovarian cancer susceptibility gene BRCA1 encodes a multifunctional tumor suppressor protein BRCA1, which is involved in regulating cellular processes such as cell cycle, transcription, DNA repair, DNA damage response and chromatin remodeling. BRCA1 protein, located primarily in cell nuclei, interacts with multiple proteins and various DNA targets. It has been demonstrated that BRCA1 protein binds to damaged DNA and plays a role in the transcriptional regulation of downstream target genes. As a key protein in the repair of DNA double-strand breaks, the BRCA1-DNA binding properties, however, have not been reported in detail. RESULTS: In this study, we provided detailed analyses of BRCA1 protein (DNA-binding domain, amino acid residues 444-1057) binding to topologically constrained non-B DNA structures (e.g. cruciform, triplex and quadruplex). Using electrophoretic retardation assay, atomic force microscopy and DNA binding competition assay, we showed the greatest preference of the BRCA1 DNA-binding domain to cruciform structure, followed by DNA quadruplex, with the weakest affinity to double stranded B-DNA and single stranded DNA. While preference of the BRCA1 protein to cruciform structures has been reported previously, our observations demonstrated for the first time a preferential binding of the BRCA1 protein also to triplex and quadruplex DNAs, including its visualization by atomic force microscopy. CONCLUSIONS: Our discovery highlights a direct BRCA1 protein interaction with DNA. When compared to double stranded DNA, such a strong preference of the BRCA1 protein to cruciform and quadruplex structures suggests its importance in biology and may thus shed insight into the role of these interactions in cell regulation and maintenance.
Keywords: B-DNA; vazba proteinů; konformace nukleové kyseliny; proteinové domény; lidé; DNA, B-Form; Nucleic Acid Conformation; Protein Binding; protein BRCA1; Protein Domains; BRCA1 Protein; Humans